The Link of Amenities, Accessibility and Ancillary with the Selection of Tourist Destinations - Dian Meliantari; Ari Apriani (UNIVERSITAS PGRI YOGYAKARTA, 2024)
Abstract Service Tourist attractions are very important in the tourism industry. Marketing of tourism services is very dependent on the state of tourist attractions There are also many attractions that are empty of visitors. There are several factors that cause tourist destinations not to be chosen by tourists, including amenities or facilities and infrastructure that are less complete and attractive. Accessibility to locations is difficult to reach by transportation and anxiliaria or unprofessional managers. So this study was conducted to analyze these factors whether they really affect the selection of tourist destinations. The method used is a quantitative method with the use of data from BPS. Further analyzed by multiple linear regression with SPSS 26. As a result, partial amenities have a significant effect and on the selection of tourist destinations. Accessibility does not have a significant effect on the selection of tourist destinations. Ansilari has a significant influence on the selection of tourist destinations. Simultaneously, amenity, accessibility and anxiety have a significant effect on the selection of tourist destinations. Keywords: Amenity, Accessibility, Ancillary, Tourist Destination, Destination Abstrak Objek wisata merupakan hal yang sangat penting dalam industry pariwisata. Pemasaran jasa pariwisata ini sangat tergantung dengan keadaan objek wisata Banyak juga objek wisata yang sepi pengunjung. Ada beberapa faktor yang menyebabkan tujuan wisata tidak dipilih oleh wisatawan, antara lain amenitas atau sarana dan prasarana yang kurang lengkap dan menarik. Aksesibilitas menuju lokasi sulit dijangkau oleh transportasi dan ansilari atau pengelola yang tidak professional. Sehingga penelitian ini dilakukan guna menganalisis faktor-faktor tersebut apakah benar berpengaruh terhadap pemilihan tujuan wisata. Metode yang digunakan adalah metode kuantitatif dengan penggunaan data dari BPS. Selanjutnya dianalisis dengan regresi linier berganda dengan SPSS 26. Hasilnya, amenitas secara parsial berpengaruh signifikan dan terhadap pemilihan tujuan wisata. Aksesibilitas tidak berpengaruh signifikan terhadap pemilihan tujuan wisata. Ansilari berpengaruh signifikan terhadap pemilihan tujuan wisata. Secara simultan amenitas, aksesibilitas dan ansilari berpengaruh signifikan terhadap pemilihan tujuan wisata. Kata Kunci: Amenitas, Aksesibilitas, Ansilari, Tujuan Wisata, Destinasi.